2021
DOI: 10.3390/rs13040765
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Summertime Primary Production Required in Changed Marine Environments in Upwelling Ecosystems Around the Taiwan Bank

Abstract: The Taiwan Bank (TB) is located in the southern Taiwan Strait, where the marine environments are affected by South China Sea Warm Current and Kuroshio Branch Current in summer. The bottom water flows upward along the edge of the continental shelf, forming an upwelling region that is an essential high-productivity fishing ground. Using trophic dynamic theory, fishery resources can be converted into primary production required (PPR) by primary production, which indicates the environmental tolerance of marine eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…During autumn, high CRs were distributed widely across the southwestern TS, including in the waters along the southwestern coast of Taiwan and between the Penghu Islands and the Taiwan Bank, and concentrated gradually in winter. Previous studies on upwelling in the TS have reported that upwelling is a yearround phenomenon, with the degree of upwelling varying in the water around the Penghu Islands and Taiwan Bank (Lan et al, 2009;Hong et al, 2011;Hsiao et al, 2021). Fronts and mesoscale eddies are formed in the Taiwan Bank through the interaction of different water masses and monsoons, which all influence larval species due to the dispersion and convergence of nutrients (Zhang et al, 2014;Hsiao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During autumn, high CRs were distributed widely across the southwestern TS, including in the waters along the southwestern coast of Taiwan and between the Penghu Islands and the Taiwan Bank, and concentrated gradually in winter. Previous studies on upwelling in the TS have reported that upwelling is a yearround phenomenon, with the degree of upwelling varying in the water around the Penghu Islands and Taiwan Bank (Lan et al, 2009;Hong et al, 2011;Hsiao et al, 2021). Fronts and mesoscale eddies are formed in the Taiwan Bank through the interaction of different water masses and monsoons, which all influence larval species due to the dispersion and convergence of nutrients (Zhang et al, 2014;Hsiao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on upwelling in the TS have reported that upwelling is a yearround phenomenon, with the degree of upwelling varying in the water around the Penghu Islands and Taiwan Bank (Lan et al, 2009;Hong et al, 2011;Hsiao et al, 2021). Fronts and mesoscale eddies are formed in the Taiwan Bank through the interaction of different water masses and monsoons, which all influence larval species due to the dispersion and convergence of nutrients (Zhang et al, 2014;Hsiao et al, 2021). Hsiao et al (2021) revealed that the fishery resource structures in the frontal habitat of the Taiwan Bank are supported by both warm-and cold-water species, including S. commerson.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate-induced habitat suitability changes may strongly influence fisheries (Kuczynski et al, 2018). For example, in the southern TS, pelagic species resources are susceptible to climate change, whereas benthic species are mainly insensitive to climatic factors (Hsiao et al, 2021). This variability may explain changes in CRs in suitable and optimal habitat areas caused by ENSO events in the TS.…”
Section: El Niño-southern Oscillation Events and Suitable Habitatsmentioning
confidence: 99%